What is the solution of the equation 8+6x=14 solving for x ? (1 point)

9 answers

The solution of the equation 8+6x=14, solving for x, is:

x=1
What is the solution of the equation x/3−9=6 solving for x ? (1 point)
To solve the equation x/3 - 9 = 6 for x, we need to isolate x on one side of the equation.

First, we can add 9 to both sides of the equation to get rid of the -9 term:

x/3 - 9 + 9 = 6 + 9

This simplifies to:

x/3 = 15

Next, we can multiply both sides of the equation by 3 to get rid of the 1/3 coefficient:

3(x/3) = 3(15)

This simplifies to:

x = 45

Therefore, the solution to the equation x/3 - 9 = 6, solving for x, is:

x = 45
Randall needs to solve the equation 5x + 8 = 63 . His first mathematical operation used to isolate x is subtraction. Which value will he apply it to?(1 point)
To solve the equation 5x + 8 = 63 by isolating x, Randall needs to subtract 8 from both sides of the equation. Thus, he will apply the subtraction operation to the term 8.
Marion is solving the equation 9x − 6 = 12 . As a first step, she adds 6 to both sides of the equation. In the next step, by what value does each side need to be divided? (1 point)
To solve the equation 9x - 6 = 12, Marion has already added 6 to both sides in her first step.

To isolate x further, the next step would be to divide both sides of the equation by the coefficient of x. In this case, the coefficient of x is 9.

Therefore, in the next step, each side of the equation needs to be divided by 9.
Beejal is solving the equation y/7 − 3 = 39.(1 point)
As a first step, he starts by adding ?
to both sides of the equation, and then continues by multiplying by ?
on each side.
To solve the equation y/7 - 3 = 39, Beejal can follow these steps:

1) As a first step, he needs to add 3 to both sides of the equation to isolate y/7. Therefore, he adds 3 to both sides:

y/7 - 3 + 3 = 39 + 3

This simplifies to:

y/7 = 42

2) In the next step, Beejal needs to multiply both sides of the equation by 7 to get rid of the 1/7 coefficient of y. Therefore, he multiplies both sides by 7:

7(y/7) = 7(42)

This simplifies to:

y = 294

So, y = 294 is the solution to the equation y/7 - 3 = 39.